Modelling a passenger car system based on the principles of sustainable mobility in Vilnius City - Grigonis, Vytautas; Burinskienė, Marija; Paliulis, Gražvydas; Ušpalytė-Vitkūnienė, Rasa; Dumbliauskas, Vytautas; Barauskas, Andrius (Transport, 2014)
The growing rate of motorization and the use of passenger cars have a worsening effect on traffic conditions in the streets of Vilnius City. Moreover, adverse urbanisation processes (i.e. migration to suburban areas) make a huge effect on the behaviour of travelling. A deeper analysis of these processes requires large data amounts and techniques for analysing transportation. The study is aimed at preparing and assessing the scenarios of developing passenger car transport through the prism of sustainability indicators. A plan for case study-based hypothetical mobility management explores a series of future scenarios improving transportation diversity and changes in modes for travellers. These scenarios are developed with respect to developments anticipated in the Master Plan of the City of Vilnius and aims at identifying the effect of a new public transport network on the motorized transport system during the morning peak in the hypothetical year 2025. Mobility management through transportation diversity increases travelling options, encourages travellers to choose the most efficient mode and tends to eliminate car dependency that otherwise occurs in urban areas. The development of a public transport route network in Vilnius City creates real preconditions for implementing a sustainable transport system thus giving a priority to the development of a new and fast transport mode. The planned routes of the new transport mode allows significantly reducing the necessity for the use of private motorized transport and influencing the total structure of travels thus making it possible for a large number of people to reach destination by public transport. First Published Online: 22 Sep 2014